Bronchoesophageal Fistula Stenting Using High-Frequency Jet Ventilation and Underwater Seal Gastrostomy Tube Drainage - Nitish Fokeerah; Xinwei Liu; Yonggang Hao; Lihua Peng (Case Reports in Anesthesiology)
Managing a patient scheduled for bronchoesophageal fistula repair is challenging for the anesthetist. If appropriate ventilation strategy is not employed, serious complications such as hypoxemia, gastric distension, and pulmonary aspiration can occur. We present the case of a 62-year-old man with a bronchoesophageal fistula in the left main stem bronchus requiring the insertion of a Y-shaped tracheobronchial stent through a rigid bronchoscope, under general anesthesia. We successfully managed this intervention and herein report this case to demonstrate the effectiveness of underwater seal gastrostomy tube drainage used in conjunction with high-frequency jet ventilation during bronchoesophageal fistula stenting.